Imposed information seeking in public libraries and school library media centers: a common behaviour? (Information Research: An International Electronic Journal)
The imposed query model provides a new way of thinking about whom the user is in information proving organizations and environments. It does this by making a distinction between questions that are self-generated (internally motivated by personal context) and those that are imposed (thought up by one person then given to someone else to resolve). While the imposed query model represents familiar behaviour, it is a dimension of information seeking that has only recently been explicitly addressed and isolated for study. This article summarizes research on the imposed query in two different information providing contexts: the elementary school and the adult reference desk at the public library. Results reveal whom the imposers and agent users are in these environments and provide an assessment of how common imposed queries are in these contexts.